Steady aircraft flight and performance - McClamroch, N. Harris (Princeton University Press, 2011)
This textbook offers a unique introduction to steady flight and performance for fixed-wing aircraft from a twenty-first-century flight systems perspective. Emphasizing the interplay between mathematics and engineering, it fully explains the fundamentals of aircraft flight and develops the basic algebraic equations needed to obtain the conditions for gliding flight, level flight, climbing and descending flight, and turning flight. It covers every aspect of flight performance, including maximum and minimum air speed, maximum climb rate, minimum turn radius, flight ceiling, maximum range, and maximum endurance. Steady Aircraft Flight and Performance features in-depth case studies of an executive jet and a general aviation propeller-driven aircraft, and uses MATLAB to compute and illustrate numerous flight performance measures and flight envelopes for each. Requiring only sophomore-level calculus and physics, it also includes a section on translational flight dynamics that makes a clear connection between steady flight and flight dynamics, thereby providing a bridge to further study.